P-091 Patients with Inflammatory Bowel Disease Who Develop Secondary Systemic Amyloidosis Have Increased In-Hospital Mortality. (February 2017) - Sharma, Prabin; Aguilar, Rodrigo; Tabanor, Joy-Ann; Mordon, Armenia; Chedid, Alice; Montero, Alex; Shammash, Jonathan; Asif Siddiqui, Omer; Li, Ping; Abi Nader, Mark
Abstract : Background: Systemic AA amyloidosis has been reported as a rare but severe complication of Inflammatory Bowel disease (IBD), particularly of Crohn's disease (CD). It is characterized by extracellular deposition of fibrillar proteins in organs leading to organ dysfunction. The aim of this study is to evaluate those risk factors and predictors of complications and in-hospital mortality of patients with Crohn's Disease (CD) and Ulcerative colitis (UC) who develop secondary systemic amyloidosis (SSA). Methods: Using the Nationwide Inpatient Sample Database, we identified patients between 2004 and 2012 with Inflammatory Bowel disease (ICD 9 Codes 555.0, 555.1, 555.2, 555.9, 556.0, 556.1, 556.3, 556.4, 556.5, 556.6, 556.8, 556.9) and secondary systemic amyloidosis (ICD 9 Code 277.39). Patients with CD were compared with those with UC for presence or absence of secondary systemic amyloidosis. All categorical variables were compared with Pearson's χ 2 test and continuous variables were analysed with paired t test. Analyses were performed using SAS version 9.3 (SAS Institute). Results: Among the 268, 170 patients with CD and 152, 804 patients with UC admitted to the hospital between 2004 and 2012, we identified 44 (0.02%) and 25 (0.02%) cases of SSA respectively. In patients with CD, SSA was significantly associated with age >51 years (47% versus 25%, P < 0.001), vitamin B12 deficiency anemia (2.3% versus 0.3%, P = 0.01), anemia of chronic disease (9.1% versus 3.4%, P = 0.03), renal osteodystrophy (2.3% versus 0.2%, P = 0.0004), acute tubular necrosis (9.1% versus 0.5% P < 0.0001), ischemic colitis (4.6% versus 0.3%, P < 0.0001), polyneuropathy (2.3% versus 0.02%, P < 0.0001) and deep vein thrombosis (2.3% versus 0.3%, P = 0.02) compared to CD patients without SSA. In-hospital mortality was also significantly higher in the CD-SSA group (9.1% versus 1.0%, P = <0.0001). On the other hand, UC patients with SSA when compared with UC patients without SSA, were significantly older >66 years (39% versus 24%, P = 0.04) and significantly associated with multiple sclerosis (4.0% versus 0.5%, P = 0.01), chronic pancreatitis (4.0% versus 0.6%, P = 0.02), chronic diastolic heart failure (4.0% versus 0.4%, P = 0.005) and pyoderma gangrenosum (6.7% versus 0.4%, P < 0.0001). In hospital mortality was again much higher for the UC patients with SSA (20% versus 2.3%, P < 0.0001). Conclusions: Secondary systemic amyloidosis is a rare disease in patients with IBD, which should be considered in CD or UC patients presenting with nephrotic proteinuria. Systemic amyloidosis appears to significantly increase in-hospital mortality of IBD patients.